Experience baking - Cariño, Celia E.; Lazaro, Amor S. (Manila, Philippines : Mindshapers Co. Inc., 2020)
This book informs the students about the history of bread making in country of its origin up to the tie when it came to the Philippines.
CHAPTER 1. History of baking -- 2. Principles involved in baking -- 3. Cookies -- 4. Cakes and icings -- 5. Pastries -- 6. Breads.
Includes bibliographical references.
Keywords: BAKING